Activation of S1PR2 on macrophages and the hepatocyte S1PR2/RhoA/ROCK1/MLC2 pathway in vanishing bile duct syndrome. - Aya Miyagawa-Hayashino; Tetsuya Imura; Toshiaki Takezawa; Maki Hirai; Saya Shibata; Hiroshi Ogi; Takahiro Tsujikawa; Eiichi Konishi (PLoS ONE)
Immunologic bile duct destruction is a pathogenic condition associated with vanishing bile duct syndrome (VBDS) after liver transplantation and hematopoietic stem-cell transplantation. As the bile acid receptor sphingosine 1-phosphate receptor 2 (S1PR2) plays a critical role in recruitment of bone marrow-derived monocytes/macrophages to sites of cholestatic liver injury, S1PR2 expression was examined using cultured macrophages and patient tissues. Bile canaliculi destruction precedes intrahepatic ductopenia; therefore, we focused on hepatocyte S1PR2 and the downstream RhoA/Rho kinase 1 (ROCK1) signaling pathway and bile canaliculi alterations using three-dimensional hepatocyte culture models that form obvious bile canaliculus-like networks. Multiplex immunohistochemistry revealed increased numbers of S1PR2+CD45+CD68+FCN1+ inflammatory macrophages and S1PR2+CD45+CD68+MARCO+ Kupffer cells in liver tissues showing ductopenia due to graft-versus-host disease and rejection post-liver transplant compared with normal liver. Macrophage expression of proinflammatory cytokines, including MCP1, was reduced following S1PR2 inhibition. Taurocholic acid and S1P2 agonist induced hepatocyte S1PR2 and reduced RhoA/ROCK1 expression, resulting in bile canaliculi dilatation. S1PR2 inhibition reversed the effect on RhoA/ROCK1 expression, resulting in maintenance of bile canaliculi through myosin light chain 2 (MLC2) phosphorylation. Activation of S1PR2 on macrophages and S1PR2 on hepatocytes may disrupt bile canaliculi dynamics in VBDS under regulation by RhoA/ROCK1 through MLC2 phosphorylation.